2022
DOI: 10.1149/2162-8777/ac9c91
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surface Roughness and Material Properties of Inert Electrodes on the Threshold Voltages and Their Distributions of ReRAM Memory Cells

Abstract: We explored the impact of the surface roughness (SR) and other material properties of metal electrodes on the statistical distributions of the switching threshold voltages, Vform, Vset, and Vreset, of a resistive memory (ReRAM) cell. The surface roughness of Pt, Ru, Co, and Cu in Cu/TaOx/Pt, Cu/TaOx/Ru, and Cu/TaOx/Co devices is extensively characterized and related to switching characteristics of the devices. We find that SF has both impact on the mean and on the standard deviation of the Vform , Vset, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…The work function difference between Ag and ITO is −0.44 eV (4.26–4.7 eV), and that between Cu and ITO is −0.05 eV (4.65–4.7 eV) [ 36 , 41 ]. The built-in field of the device was determined using the following expression [ 40 ]: where E bi represents the built-in field, Δ Φ is the difference between the work function of the TE and BE, q is the charge amount, and t ox is the oxide thickness (55 nm). The E bi obtained for the Ag device was 0.8 × 10 5 V·cm −1 , while that for the Cu device was 0.09 × 10 5 V·cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The work function difference between Ag and ITO is −0.44 eV (4.26–4.7 eV), and that between Cu and ITO is −0.05 eV (4.65–4.7 eV) [ 36 , 41 ]. The built-in field of the device was determined using the following expression [ 40 ]: where E bi represents the built-in field, Δ Φ is the difference between the work function of the TE and BE, q is the charge amount, and t ox is the oxide thickness (55 nm). The E bi obtained for the Ag device was 0.8 × 10 5 V·cm −1 , while that for the Cu device was 0.09 × 10 5 V·cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…For micro size asperities with c = 16 μm and b = 0.7 μm one obtains an enhancement factor of β = 187. Countless studies have confirmed since then the impact of the electric field enhancement factor on various physical systems [34].…”
Section: Surface Roughness Studies Of Ru Pt Co and Cumentioning
confidence: 92%
“…For a more detailed discussion of how the field enhancement factor correlates with SR, see ref. [34]. The differences in SR explain that in order to reach a critical field required for the formation of a filament a lower voltage is needed in case of a rougher surface of Co than for smoother interfaces of Pt or Ru.…”
Section: Electric Characteristics Of the Ruthenium (Cu/tao X /Ru)mentioning
confidence: 99%
See 2 more Smart Citations